Gestión de peticiones, quejas y reclamos PQR bajo metodología RUP para la Fundación Clínica del Norte (2018)
The customer service is a fundamental process in the companies that provide a service and institutions providers of health - IPS, especially, should provide channels for users to exercise their constitutional right, and to comply with the parameters the Superintendence of health surveillance. Once detected the need of a tool for the management of PQR in the Clinic North Foundation, proposes a development with his measure, which meets the need, be able to make traceability and management; In addition, that are believed service channels to users. To get to the detection of the specific need of the Clinic of the North, inquiries, conducted through a formal interview to ascertain the current status and propose a future State. In the development of the application, the RUP (Rational Unified Process) methodology was used.